Tax knowledge, tax ethics and tax non compliant behavior of non-accounting postgraduates from Universiti Teknologi MARA (UiTM), Shah Alam / Mira Susanti Amirrudin - Amirrudin, Mira Susanti (2007)
The objective for implementation of the self-assessment tax system (SAS) is to increase voluntary tax compliance among taxpayers. Under SAS, taxpayers are required to compute their own tax liability. Hence, taxpayers need to have basic personal tax knowledge to fill out tax return form correctly and accurately. To help them reduce tax liability within the tax laws, taxpayers need to understand the differences between tax evasion, tax avoidance and tax planning. This study aims to assess the level of tax knowledge of postgraduates from non-accounting disciplines and examine their tax ethical beliefs. In addition, the study attempts to identify whether they understand the differences between tax evasion, tax avoidance and tax planning and to seek their opinions about the introduction of tax subject at non-accounting postgraduate's level. A survey was used to collect data from seven non-accounting faculties in Universiti Teknologi MARA, Shah Alam. A total of 620 questionnaires were distributed and the response rate was 35.97% (223/620). The findings indicated that 640/0 of respondents (who are taxpayers) had medium level of knowledge in personal taxation. About 62.80/0 of respondents (who are taxpayers) showed negative level of tax ethics. Interestingly, majority of respondents were unable to define and classify tax behaviours into tax evasion, tax avoidance or tax planning correctly. The level of tax knowledge for those who had studied taxation is higher than those that had not studied taxation. Furthermore, the tax ethics score for male is higher than female which indicates that male taxpayers had higher negative tax ethics level than female. In addition, there is significance difference in the taxpayers experience and the level of tax knowledge. Only 37.7% of respondents favoured that tax subject be introduced in their course.